Research on Natural Gas Data Management Model and Operation Mechanism Based on DCMM - Liu, Qin; Cao, Zhengyan (International Journal of Natural Resources and Environmental Studies, 2025)
To respond to the national policies on the development and utilization of enterprise data resources and promote the digital and intelligent transformation of the natural gas industry, this paper first reviews the research status of data management models, natural gas data management, and the Data Management Capability Maturity Assessment Model (DCMM). Subsequently, it analyzes the characteristics of natural gas data management, such as high integration and real-time accuracy, as well as existing issues including data silos, insufficient data quality, and lack of standardization, and points out that current assessments focus on security and value. Furthermore, the paper constructs a natural gas data management capability maturity assessment model based on DCMM(DCMM-NG), defining 8 core capability areas, 5 maturity levels, and the assessment process. Finally, it proposes that DCMM needs to be adjusted in accordance with industry characteristics; this model can help enterprises identify the strengths and weaknesses of their data management and provide support for formulating targeted improvement strategies.